Systemic treatment of HER2‐positive metastatic breast cancer: A systematic review. (June 2014) - Wilcken, Nicholas; Zdenkowski, Nicholas; White, Michelle; Snyder, Ray; Pittman, Ken; Mainwaring, Paul; Green, Michael; Francis, Prudence; De Boer, Richard; Colosimo, Maree; Chua, Sue; Chirgwin, Jacquie; et al.
Abstract: Aim: We aimed to systematically review and summarize data from the available clinical trials that examined the treatment of HER2‐positive metastatic breast cancer. Methods: We reviewed phase 2 and 3 studies in which an anti‐HER2 agent was used in one or both arms of the study. While formal meta‐analysis was not possible for such a heterogeneous group of trials, resulting forest plots outline some generalizable findings. Results: There is strong evidence that the addition of an anti‐HER2 agent to standard chemo‐ or endocrine therapy improves clinically relevant measurable outcomes. There is also consistent evidence that initial treatment with trastuzumab alone (and subsequent use of a cytotoxic) is inferior to the initial combination of trastuzumab plus chemotherapy, and that either T‐DM1 or dual anti‐HER2 agents are superior to single anti‐HER2 agent regimens. There is no strong evidence that the use of more than one cytotoxic agent together with an anti‐HER2 agent confers any benefit over a single cytotoxic, anti‐HER2 combination. Conclusion: This review provides a strong evidence base for current clinical practice with a discussion of treatment in the Australian setting.